The social media MBA guide to ROI : how to measure and improve your return on investment - Holloman, Christer (Chichester, West Sussex, United Kingdom : John Wiley and Sons Ltd, 2014)
"The first book to explain how you can measure social media ROI across multiple departments, for internal/external social media based activities, as well as for new business models (product/services). This book provides help in establishing a thorough social media plan, examining your goals, audience and channel strategy, before examining tools and techniques to measure social media metrics and key performance indicators. This book debunks the myth that ROI, web metrics and social media measuring is a 'black art', and makes it easy to understand and use, enabling the reader to create bespoke ROI metrics and improve the return on activity. Practical, straightforward and informed by the key principles which the author has explored in his Social Media MBA, this transformative look at ROI will inspire a move away from 'Likes', 'Followers' and 'mentions' and towards pounds, euros and dollars"--
Strategy -- Measure ROI by Platform. Facebook -- Twitter -- YouTube -- LinkedIn -- Google+ -- Pinterest -- Blogs --Tools. Choosing a supplier -- Popular measuring platforms -- Case Studies. Ob2 (B-Customer service -- Sabre Hospitality Solutions- business development -- Makino- sales -- giffgaff- customer retention -- BRAVEday Insurance- communication -- Beats by Dr. Dre- viral campaign -- Safeguarding ROI.s
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: Social media -- Management; Rate of return; BUSINESS & ECONOMICS -- E-Commerce -- Internet Marketing; Electronic books; Electronic books